2021
DOI: 10.1101/2021.01.06.425589
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dysregulation of the basal ganglia indirect pathway prior to cell loss in the Q175 mouse model of Huntington’s disease

Abstract: The psychomotor symptoms of Huntington’s disease (HD) are linked to degeneration of the basal ganglia indirect pathway. To determine how this pathway is perturbed prior to cell loss, optogenetic- and reporter-guided electrophysiological interrogation approaches were applied to early symptomatic 6-month-old Q175 HD mice. Although cortical activity was unaffected, indirect pathway striatal projection neurons were hypoactive in vivo, consistent with reduced cortical input strength and dendritic excitability. Down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 132 publications
(235 reference statements)
0
2
0
Order By: Relevance
“…Additionally, Barry, Akopian, Cepeda, and Levine (2018) showed reduced GABA release in SNr by dSPNs in R6/2 mice, and they attributed this effect to reduced activity of dSPNs. Similarly, in heterozygous Q175 mice at 6 months of age, Bevan and coworkers have shown that iSPNs show decreased responses to cortical activation (Callahan & Bevan, 2019). Thus, the presently observed increase in ENK+ striato‐GPe terminals and SP+ striato‐GPi/SN terminals in Q175 mice may, at least in part, reflect reduced neuronal firing of SPNs, and as a result, reduced neurotransmitter release by their terminals in GPe and GPi/SNr.…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, Barry, Akopian, Cepeda, and Levine (2018) showed reduced GABA release in SNr by dSPNs in R6/2 mice, and they attributed this effect to reduced activity of dSPNs. Similarly, in heterozygous Q175 mice at 6 months of age, Bevan and coworkers have shown that iSPNs show decreased responses to cortical activation (Callahan & Bevan, 2019). Thus, the presently observed increase in ENK+ striato‐GPe terminals and SP+ striato‐GPi/SN terminals in Q175 mice may, at least in part, reflect reduced neuronal firing of SPNs, and as a result, reduced neurotransmitter release by their terminals in GPe and GPi/SNr.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, arkypallidal GPe neurons and STN neurons were hypoactive. Notably, the hypoactivity of STN and arkypallidal GPe neurons was partially alleviated by optogenetic inhibition of prototypic GPe neurons ( Callahan et al, 2021 ). Another recent study identified a subnetwork of direct pathway MSNs specifically targeting arkypallidal Npas-positive neurons in the GPe ( Cui et al, 2021 ).…”
Section: Striatal Output Structuresmentioning
confidence: 99%